“CONVERSATION ANALYSIS OF ADJACENCY PAIRS ON ARIEL WENGROFF’S CONVERSATION WITH MALALA YOUSAFZAI” - Nurhayati Nurhayati; Nur Maria; Lilis Suryani (IKIP Siliwangi, 2020)
This research is a study about adjacency pairs and preference organization which are uttering a conversation between Ariel Wengroff’s with Malala Yousafzai. The objectives this study are to find out kinds of adjacency pairs and preference organization on Ariel Wengroff’s conversation with Malala Yousafzai. This research is qualitative research which describes and explains the analysis by using the words. The principle information of the research is a script of interview between presenter Ariel Wengroff and Malala Yousafzai. The data were video and script which took place at the UN headquarters in New York published on April 27, 2017 and the duration was 8:36 minute. The video was transcribed into the script and discovered that there were 12 turns. At that point it was analyzed dependent on theory by Paltridge about adjacency pairs. From the data it was founded that there were 6 adjacency pairs that consisted of 2 pairs of question – answer, and 4 pair of assessment – agreement. There were also 6 preference organization that consisted of 6 preferred responses on the conversation. Keywords: Analysis, Adjacency, Preference Organization